Woody vegetation dynamics in a floodplain campo de murundus in central Brazil - Pinto, José Roberto Rodrigues (2014)
Campos de murundus (grasslands dotted with knolls that are covered with savanna-like woody vegetation) are a common landscape in central Brazil. In this study, we assessed for the first time the dynamics of the vegetation in a floodplain campo de murundus, describing changes in composition and structure of the woody vegetation. In 2005, we established 16 permanent 25 × 25 m plots, where we identified and mapped individuals with a trunk diameter at the base ≥ 2.86 cm, as well as measuring the height of those individuals. In 2008 (after two fire events), we resampled the plots. In 2005, we had registered 4.54 m2 ha-1 of basal area, 430 individuals, 42 species, 36 genera and 24 families. In 2008, we found an increase in basal area (to 4.65 m2 ha-1) and a decrease in numbers of individuals (to 399), species (to 41), genera (to 35) and families (to 23). Species diversity did not differ between the two surveys. Mortality exceeded recruitment (2.68% year-1 vs. 1.29% year-1 ). Nevertheless, the community showed a gain in basal area owing to the growth of surviving individuals and, particularly, to the rise in the number of basal sprouts. We argue that the small floristic turnover may be related to the great resilience of the woody vegetation, whereas the structural changes might reflect the effects of the burnings in the area.